2021
DOI: 10.3390/jpm11090829
|View full text |Cite
|
Sign up to set email alerts
|

α4β1 and αMβ2 Integrin Expression and Pro-Proliferative Properties of Eosinophil Subtypes in Asthma

Abstract: Eosinophilic inflammation is one of the main pathophysiological features in asthma. Two subtypes of eosinophils exist in the lung and systemic circulation: lung-resident eosinophils (rEOS) and inflammatory eosinophils (iEOS). We evaluated the expression of α4β1 and αMβ2 integrins of eosinophil subtypes and their influence on airway smooth muscle (ASM) cell proliferation and viability in asthma. We included 16 severe non-allergic eosinophilic asthma (SNEA) patients, 13 steroid-free, non-severe allergic asthma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Esnault et al compared the effects of β-chain cytokines on eosinophil biology and demonstrated that IL-3 has a stronger effect than any other βc family cytokines in activating eosinophils [ 14 ]. However, despite the strong effect of IL-3 on eosinophil activity, the effects might be related to the stronger affinity to eosinophil IL-3 receptors rather than concentration in asthmatic patients’ blood [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Esnault et al compared the effects of β-chain cytokines on eosinophil biology and demonstrated that IL-3 has a stronger effect than any other βc family cytokines in activating eosinophils [ 14 ]. However, despite the strong effect of IL-3 on eosinophil activity, the effects might be related to the stronger affinity to eosinophil IL-3 receptors rather than concentration in asthmatic patients’ blood [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phenotyping of eosinophils was based on magnetic bead-conjugated antibodies against L-selectin. These procedures are described in detail in [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations